Identifying need for spay and neuter services: A GIS-based analysis - Cameron R. Carow; Joann M. Lindenmayer (CABI, 2023)
Abstract This study provides a method for assessing the need for spay and neuter services in Massachusetts by creating a composite index that accounts for spatial accessibility and social vulnerability. An accessibility index (AI) of existing low-cost spay/neuter (S/N) facilities was created using the two-step floating catchment area (2SFCA) method which was then combined with the social vulnerability index (SVI) from the Centers for Disease Control and Prevention to create a need index (NI). Two methods for selecting the final target areas from the NI results were examined and used to make recommendations for S/N funding allocation. The construction of the NI (i.e. factors included or weights applied to factors) had a significant impact on the results. The NI displayed statistically significant spatial autocorrelation, and hot spot analysis revealed statistically significant clusters of comparatively high- and low-need regions in the state. The target areas identified were strongly influenced by high levels of social vulnerability in urban areas and low spatial accessibility of low-cost S/N facilities in more rural western Massachusetts. The results of this project demonstrate the utility of geographic information systems (GIS)-based analysis in veterinary and shelter medicine, as well as the potential for the use of non-veterinary specific data, such as the CDC SVI, when planning the equitable distribution of limited resources. One Health impact statement Providing spay and neuter (S/N) services to owned and free-roaming cats, dogs and other companion animal species is integral to the health and well-being of the animals themselves. Their human companions also reap the physical and mental health benefits of the human-animal bond, in addition to the environmental and public health impact of limiting free-roaming dog and cat populations. By recognizing the relationships between human and animal populations, existing gaps in need can be addressed through the use of human data to inform decisions on animal health when relevant animal health service data are lacking. A composite index of factors accounting for the social vulnerability was combined with the spatial accessibility of existing S/N resources to create a final index of need for S/N resources. This transdisciplinary approach takes methodologies from public health, acknowledges the impact of the vulnerability of human populations on surrounding companion animal populations, and applies a practical method of identifying the need for specific veterinary medical services.